Rola prawnika jako argument w obronie etyki kodeksowej - Kaczmarek, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The purpose of the article is to present arguments for understanding the code of ethics as a framework of: rules within which a lawyer should move, and goals to be pursued. I intend to carry out this task in three stages. Firstly, I shall present the main accusations that are put against codex ethics. This argument claims that the codical nature of professional ethics leads or may lead to marginalisation of moral responsibility and loss of subjective agency. Then I will proceed to defend codex ethics. To this end, I refer to the concept of role, showing that the conflict situation in the legal profession is a feature of this profession. Therefore, it is necessary to build an institutional framework that allows coordinated activity in the face of various tensions. This argument reinforces the presence of the code of etics as a safeguard against the lawyer, leaving the role in a conflict related to professional activities. The purpose of this protection is to protect the client.
Keywords: lawyer; professional role; codex ethics; moral responsibility